2016
DOI: 10.22452/mojem.vol4no3.4
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Validity of Gender and Experience of Teachers Into Malaysian Women Principal’s Instructional Leadership Practices

Abstract: Malaysia, as a developing country, highly depends on its education system to achieve the Vision 2020 goal of being a developed nation. Therefore school leadership plays a key role in educational settings. As a great number of women principals are involved in leadership positions in this context, this study examined the factors influencing women principal's instructional leadership practices from teachers' perceptions through a survey instrument distributed to 39 Federal Territory of Kuala Lumpur public seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…Female principals achieved significantly higher ratings on four instructional leadership functions and male principals on one. Although these results are partially in line with the international finding of stronger instructional leadership exercised by female principals Mannan et al, 2016;Poovatanikul, 1993;Yang, 1996), the mixed results suggest a need for cautious interpretation. The need for caution is further reinforced by the fact that even in cases where "statistically significant differences" were identified in this study, both male and female principals were perceived to be enacting the functions at a "high level" (see Table IV ).…”
Section: Patterns Of Instructional Leadershipsupporting
confidence: 50%
“…Female principals achieved significantly higher ratings on four instructional leadership functions and male principals on one. Although these results are partially in line with the international finding of stronger instructional leadership exercised by female principals Mannan et al, 2016;Poovatanikul, 1993;Yang, 1996), the mixed results suggest a need for cautious interpretation. The need for caution is further reinforced by the fact that even in cases where "statistically significant differences" were identified in this study, both male and female principals were perceived to be enacting the functions at a "high level" (see Table IV ).…”
Section: Patterns Of Instructional Leadershipsupporting
confidence: 50%
“…While a majority of these studies found positive differences in favor of stronger instructional leadership from female principals, the correlations tended to be weak (e.g. Abdullah and Kassim, 2011; Agalita, 2014; Jahet, 1998; Mannan et al , 2016; Nor Rida, 2012; Yusoh, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The behavior of instructional leadership is very important for making the educational environment effective in schools. (Mannan, Sharma, Hoque, & Veeriah, 2017) The school"s instructional leader endorse effective instruction by keeping the educators wellinformed about novice educational strategies, technologies, and other methodologies for boosting the teaching-learning process in schools. (Sosibo & Allie, 2017) put forward that instructional leaders develop such staff development programs which assure to increase the effectiveness of teachers which in turn would elevate the student outcomes.…”
Section: ___________________________________________________________________________mentioning
confidence: 99%